The aesthetics of the place in Al-Pansion novel- Abdullah Alnuaimi - Alyammahi, Shaimaa; Bouali, AbdulRahman; Al-Hashemi, Badeeah (Al-Adab Journal, 2024)
The presence of the place in the novel is not just a background for the events of the novel, it is an essential element in presenting the event and the characters, and an indispensable condition in any novel, whatever its topic, as there is no story without a place, and the story is not complete without a place that embraces it, and a space in which events develop and grow. Between the place and the rest of the elements (such as events, time, and characters) is a relationship of integration. We cannot drop one of them because of the importance of his presence in the story. who lives it; It is the first reference for man, as he clung to it and built his life through it, so he became of social, psychological and psychological dimensions.This study seeks to shed light on the aesthetics of the place in the novel The Pansion by the novelist Abdullah Al-Nuaimi, by following the analytical descriptive approach. The research begins with an introduction, followed by the hadeeth of the place and its definitions, then the types of place, followed by the analysis of the geographical place and standing on its indications, then the conclusion and the results of the research.